Orchestrating Hybrid Cloud Deployment: An Overview. - Sturrus, Edwin; Kulikova, Olga (Computer (00189162), 2014)
Balancing enterprise control over cloud data with hybrid cloud benefits will increasingly require cloud "orchestration."